Generalized Rational Evaluation Subgroups of the Inclusion between Complex Projective Spaces - Gatsinzi, Jean-Baptiste (Armenian Journal of Mathematics, 2023)
We use a model of mapping spaces to compute the generalized rational Gottlieb groups of the inclusion i_n,k: CP^n CP^n+k between complex projective spaces.